2013
DOI: 10.1089/fpd.2012.1326
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bioluminescent Escherichia coli to Determine Retention During the Life Cycle of the Housefly, Musca domestica (Diptera: Muscidae, L)

Abstract: Researchers have documented that the housefly (Musca domestica) can serve as a vector for the spread of foodborne pathogens to livestock, food, and humans. Most studies have investigated Musca domestica as a vector only after the fly comes into contact or consumes the pathogen as an adult. The objective of this study was to determine whether the larvae of Musca domestica could ingest Escherichia coli from bovine manure and whether the E. coli could survive the metamorphosis process and be transmitted. Larvae (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…Although E. coli O157:H7 was present in samples containing pooled house fly eggs, this pathogen did not persist throughout metamorphosis. This finding was opposite to other studies that have reported the ingestion of non-pathogenic E. coli by house fly larva and their persistence throughout pupae and newly emerged adults [ 48 , 49 ]. However, in this study we did not quantify the amount of E. coli O157:H7 present in the larval rearing substrate; hence, the levels of this pathogen that were likely to be ingested by house fly larvae were unknown and probably low enough to avoid their persistence through the house fly life cycle.…”
Section: Resultscontrasting
confidence: 99%
“…Although E. coli O157:H7 was present in samples containing pooled house fly eggs, this pathogen did not persist throughout metamorphosis. This finding was opposite to other studies that have reported the ingestion of non-pathogenic E. coli by house fly larva and their persistence throughout pupae and newly emerged adults [ 48 , 49 ]. However, in this study we did not quantify the amount of E. coli O157:H7 present in the larval rearing substrate; hence, the levels of this pathogen that were likely to be ingested by house fly larvae were unknown and probably low enough to avoid their persistence through the house fly life cycle.…”
Section: Resultscontrasting
confidence: 99%
“…Taken in conjunction with previous data (Kobayashi et al ., ; Sasaki et al ., ), this indicates that house flies potentially serve as significant reservoirs of this pathogen for at least 12 h. Interestingly, recent work by Schuster et al . () has shown that house fly larvae that fed on E. coli ‐contaminated substrate carried bacteria trans‐stadially and newly eclosed flies harboured as many as 50 CFU. The possibility of trans‐stadial survival of E. coli O157:H7 deserves further study as this would complicate the epidemiological picture.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a preferential substrate, the flies search for alternative substrates (D'ALMEIDA; MELLO, 1996). Moreover, adult flies can retain pathogenic bacteria acquired in the larval phase (SCHUSTER et al, 2013).…”
Section: Discussionmentioning
confidence: 99%